Internalization strategy of conscious awareness of spices lane as national brand and national pride of Indonesian nation - Setiawan, Budiana; Widiputera, Ferdi (Technium Social Sciences Journal, 2020)
The archipelago (now Indonesia) in the past was known as the center of the spice commodity, which was needed for various purposes by other nations, such as: China, India, the Middle East, and Europe. This has caused the archipelago to become a destination for traders from other countries for thousands of years, thus creating a trade route called the Spice Route. The glory of the Spice Route in the Archipelago reached its peak in 1500 until 1650, but then collapsed after being ruled by European nations. Nevertheless, the existence of the history of the Spice Track needs to be internalized to students as one of the nation's branding and nation pride of the Indonesian people. The problems are: (1) What is the strategy of internalizing the teaching of the Spice Path to students? (2) What are the efforts made by the government, to support efforts to internalize the historical awareness of the Spice Track? The aim is to instill awareness to the younger generation about the glory of the Indonesian people in the past as a producer of spices. The results showed that the strategy undertaken by the Government of the Republic of Indonesia to internalize the history of the Spice Track to the younger generation was through: exhibitions, historical visits, and discussions / seminars. However, the internalization effort has not been evenly carried out in all provinces, districts and cities. To that end, internalization of the history of the Spice Route can also be done through museum visits, especially provincial state museums located in provincial capitals. Awareness about the history of the Spice Route can also be used to break the efforts of the Chinese government to promote the Maritime Silk Road for their political trade interests.